THE LEGAL FRAMEWORK OF LOCAL GOVERNMENT POLICY IN ADMINISTERING HOUSING AND SETTLEMENT AREAS IN BULELENG REGENCY - Suastawan, Nyoman Adi; Styawati, Ni Komang Arini; Rideng, I Wayan (jfpublisher, 2025)
The regulation and policy framework established by the Buleleng Regency Government concerning the administration of housing and settlement areas demonstrates a strategic legal approach to spatial development. This research examines the normative design and practical enforcement of housing governance in Buleleng Regency, with particular attention to the legal effectiveness of Regent Regulation No. 40 of 2023 as the implementing instrument of Regional Regulation No. 12 of 2022 on the Administration of Housing and Settlement Areas. Employing an empirical legal research method, the study investigates the gap between written law (law in books) and actual practice (law in action) using a juridical-analytical approach. Primary data were collected through interviews and subsequently analyzed qualitatively in conjunction with legal theories, academic literature, and statutory regulations. The findings indicate that the provision on the minimum access road width, as stipulated in the Regent Regulation, has been relatively effective in practice. However, a significant number of developers continue to carry out housing development outside of the designated residential zones. One of the main implementation challenges lies in the fact that many plots located within housing and settlement zones do not meet the required road width standard, thereby complicating compliance with the regulation.